2014
DOI: 10.1111/1744-9987.12174
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal Muscle Loss Is Negatively Associated With Single‐Pool Kt/V and Dialysis Duration in Hemodialysis Patients

Abstract: We evaluated the skeletal muscle loss in hemodialysis (HD) patients by bioelectrical impedance analysis (BIA) and handgrip strength test. Thirty-four HD patients and 16 healthy subjects (control group) were measured for skeletal muscle mass normalized as the skeletal muscle mass index (SMI), calculated as skeletal muscle mass (kg)/height (m)(2) using a tetrapolar bioelectrical impedance plethysmograph. Handgrip strength test was also performed using a hand dynamometer in both groups. In HD patients, the associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 26 publications
3
10
1
Order By: Relevance
“…The Kt/V results in the present study were associated with a loss of ASM in the patients. These results were consistent with those of Morishita et al, who demonstrated that Kt/V was negatively associated with both muscle mass and handgrip strength in 34 HD patients [ 37 ]. It implies that patients with a low muscle mass may require a higher clearance in relation to the volume of urea distribution.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The Kt/V results in the present study were associated with a loss of ASM in the patients. These results were consistent with those of Morishita et al, who demonstrated that Kt/V was negatively associated with both muscle mass and handgrip strength in 34 HD patients [ 37 ]. It implies that patients with a low muscle mass may require a higher clearance in relation to the volume of urea distribution.…”
Section: Discussionsupporting
confidence: 93%
“…We found no relationship between dialysis vintage and muscle mass among the patients, even though a previous study revealed that the loss of SMM was negatively associated with dialysis vintage [ 37 ]. The inconsistency in the results of the relationship between dialysis vintage and muscle mass can be explained as follows: the HD patients in our study (i) were relatively young (61.4 ± 10.4 years versus 66.9 ± 9.6 years), (ii) had a relatively short dialysis vintage (5.4 ± 5.3 years versus 6.3 ± 4.7 years), and (iii) had a high SMM index, analyzed using a similar BIA equipment (9.1 ± 1.4 kg/m 2 versus 4.6 ± 1.0 kg/m 2 ).…”
Section: Discussioncontrasting
confidence: 83%
“…30 We previously reported that skeletal muscle mass and muscle strength decreased in accordance with duration on hemodialysis, even after adjustment for age and sex. 31 We also reported that physical activity is positively associated with muscle mass in hemodialysis patients. 32 A questionnaire survey of exercise habits in 2,264 hemodialysis and peritoneal dialysis patients found that 795 (35.1%) of these patients exercised little or not at all.…”
Section: Hemodialysis Patientsmentioning
confidence: 64%
“…We previously reported that sarcopenia progressed in accordance with duration on hemodialysis even after adjustment for age and sex ( 21 ). Sarcopenia is a strong predictor of mortality in hemodialysis patients as well as in CKD patients at the pre-dialysis stage ( 14 - 19 ).…”
Section: Resultsmentioning
confidence: 98%